Biochemiceskie aspekty korrekcii pitanija borcov - Artemyeva, N. K.; Lipatnikova, M. A.; Stepurenko, V. V.; Lavricenko, S. P.; Ivanov, I. I. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The complex researches specify the progressing deterioration of the meal base of athletes. The attempts of the majority of researchers to correct meals by the introduction of additives of functional purpose are characterized by unilateral approaches. Besides the experts frequently underestimate the interrelation of the ergogenetic effect of the additives and the metabolic dynamics during the individual adaptation to the muscular activity of a various character.